High valuable compounds from the unripe peel of several Musa species cultivated in Madeira Island (Portugal) - Jose Villaverde, Juan
The lipophilic extractives of the unripe peel of ten banana cultivars belonging to the Musa acuminata and Musa balbisiana species (namely 'Giant Cavendish', 'Chinese Cavendish', 'Grand Nain', 'Gruesa', 'Williams', 'Ricasa', 'Eilon', 'Zelig', 'Dwarf Red' and 'Silver') were studied by gas chromatography-mass spectrometry. The extractives content were in the range of 2-3% with substantially higher values for 'Silver' and 'Dwarf Red' (5.7 and 10.7% respectively). Sterols and fatty acids were the major families of compounds identified, with respectively 55.1-87.5% and 10.6-43.2% of total of lipophilic components. Cycloeucalenone was the main component identified in 'Williams' and 'Dwarf Red', with abundances ranging from 806 to 9453 mg Kg(-1) of dry unripe peels, respectively. The identification of high contents of valuable compounds, can open new strategies for the valorization of the studied banana residues and particularly of those from 'Dwarf Red' followed by 'Silver' and 'Ricasa', as potential sources of high-value phytochemicals. (C) 2012 Elsevier B.V. All rights reserved.